Alternatif Penanganan Dampak Pandemi Covid-19 Melalui Sosialisasi dan Pelatihan Teknologi - Indriyani Indriyani; Paula Dewanti; Komang Bhargo Bhaskara (Yayasan Literasi Sains Indonesia, 2022)
These community service activities were intended to ease the burdens on people impacted by the Covid-19 pandemic, especially from a financial standpoint. The implementation process was carried out offline and online, utilizing the technology. The event begins with a technology dissemination talk, an education on how to grow crops through the hydroponic method, then continued with a technology education in the form of Design classes, Webinars with the topic of learning and business in the new normal era, and closed with ceremonial, photos sessions, along with the delivery of donations.